The value of a feasibility study into long‐term macrolide therapy in chronic rhinosinusitis. (20th June 2016) - Bewick, J.; Ahmed, S.; Carrie, S.; Hopkins, C.; Sama, A.; Sunkaraneni, V.; Woods, J.; Morris, S.; Erskine, S.; Philpott, C.M.
Abstract : Objectives: There is currently conflicting level 1 evidence in the use of long‐term antibiotics for chronic rhinosinusitis without nasal polyps. The primary aim of this feasibility study was to optimise future randomised trial design by assessing recruitment and retention of patients alongside providing preliminary data on symptomatic control. Design: Prospective, multicentre feasibility (cohort) study with all patients receiving macrolide therapy for 12 weeks and a further subsequent 12‐week follow‐up. Participants received a 12‐week course of clarithromycin 250 mg alongside twice daily topical mometasone and nasal douching. Primary outcomes focused on recruitment, retention and compliance. Clinical and quality‐of‐life outcomes measures were also recorded. Setting: Patients were prospectively recruited from six UK outpatient clinics. Participants: Adult patients with chronic rhinosinusitis without nasal polyps and no prior endoscopic sinus surgery underwent baseline assessment and then follow‐up at 3 and 6 months. Main outcome measures: Six‐month recruitment and retention data. Results: Over 13 months, 55 adults were recruited from five centres. Four patients declined participation. 75% of patients were retained within the study. Dropouts included one medication contraindication, three unable to tolerate medication and 10 not attending full follow‐up. Sino Nasal Outcome Test‐22 and endoscopic scores showed statistically significant improvement. No other clinical or quality‐of‐life assessment improvements were seen. Conclusion: Retention and recruitment to a trial using long‐term clarithromycin to treat chronic rhinosinusitis without nasal polyps is achievable and this data will support a future randomised controlled trial. The study provides vital insight into trial design, thus informing UK research networks and rhinology researchers internationally.